The way of the modern warrior living the samurai ideal in the 21st century - Kaufman, Stephen 1939- Hanshi
The modern warrior applies his or her total energy and creativity in support of a just cause to resolve conflicts and promote the greater good. Their mission demands emotional wellbeing and intellect as well as strength. This book presents the ancient samurai warrior ethos developed and practiced in Japan for over 1000 years-the greatest expression of the warrior's code which the world has ever seen-as it applies to today's modern warrior. It is an essential handbook for those who are willing to live and die by the warrior's side